RISIKO KEUANGAN DAN PENGARUHNYA TERHADAP PROFITABILITAS BANK SYARIAH DI INDONESIA - Pani Akhiruddin Siregar (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2020)
Research aims to test financial risk and influence on the profitability of Sharia Bank in Indonesia. Financial risk indicators include CAR, NPF, BOPO, FDR and ROE. Profitability indicators of Sharia Banks in Indonesia are ROA. The research method uses a quantitative approach with multiple linear regression analysis techniques. Data used secondary data in the form of a monthly data From The Financial Report of Sharia Commercial Bank and Sharia Business Unit published by Sharia Banking Directorate, Bank Indonesia and the Bank Licensing and Banking Information Department, Indonesia Financial Services Authority from January 2006 to January 2018. Research results: (1)The result of the model estimate shows its R2 value of 0,614 representing the value of coefficient of determination. This means that 61,40% of the variable variations of the ROA are capable of being described by independent variable in this model. The remaining 38,60% is explained by other reasons that do'nt fit into the model; (2)A regression model on the independent variable simultaneously affects the dependent variable, so that the independent variable regression model can be used to predict the dependent variable; and (3)CAR, NPF and FDR are significantly influence on ROA. BOPO and ROE influential on ROA. But, it's not significant.